De Novo Assembly of Plasmodium knowlesi Genomes From Clinical Samples Explains the Counterintuitive Intrachromosomal Organization of Variant SICAvar and kir Multiple Gene Family Members - Oresegun, Damilola R.; Thorpe, Peter; Benavente, Ernest Diez; Campino, Susana; Muh, Fauzi; Moon, Robert William; Clark, Taane Gregory; Cox-Singh, Janet (Frontiers in Genetics, 2022)
Plasmodium knowlesi, a malaria parasite of old-world macaque monkeys, is used extensively to model Plasmodium biology. Recently P. knowlesi was found in the human population of Southeast Asia, particularly Malaysia. P. knowlesi causes un-complicated to severe and fatal malaria in the human host with features in common with the more prevalent and virulent malaria caused by Plasmodium falciparum. As such P. knowlesi presents a unique opportunity to develop experimental model systems for malaria pathophysiology informed by clinical data from same-species human infections. Experimental lines of P. knowlesi represent well characterised genetically static parasites and to maximise their utility as a backdrop for understanding malaria pathophysiology, genetically diverse contemporary clinical isolates, essentially wild-type, require comparable characterization. The Oxford Nanopore PCR-free long-read sequencing platform was used to sequence and de novo assemble P. knowlesi genomes from frozen clinical samples. The sequencing platform and assembly pipelines were designed to facilitate capturing data and describing, for the first time, P. knowlesi schizont-infected cell agglutination (SICA) var and Knowlesi-Interspersed Repeats (KIR) multiple gene families in parasites acquired from nature. The SICAvar gene family members code for antigenically variant proteins analogous to the virulence-associated P. falciparum erythrocyte membrane protein (PfEMP1) multiple var gene family. Evidence presented here suggest that the SICAvar family members have arisen through a process of gene duplication, selection pressure and variation. Highly evolving genes including PfEMP1family members tend to be restricted to relatively unstable sub-telomeric regions that drive change with core genes protected in genetically stable intra-chromosomal locations. The comparable SICAvar and KIR gene family members are counter intuitively located across chromosomes. Here we demonstrate that, in contrast to conserved core genes, SICAvar and KIR genes occupy otherwise gene-sparse chromosomal locations that accommodate rapid evolution and change. The novel methods presented here not only offer the malaria research community new tools to generate comprehensive genome sequence data from small clinical samples but new insight into the complexity of clinically important real-world parasites.